BETTER SELL BAGASSE THAN SURPLUS ELECTRICITY? - Jaguaribe, E. F.; Lobo, P. C.; de Souza, W. L.; Rocha, R. M.; Nascimento, E. T. (Revista de Engenharia Térmica, 2007)
Over the past decade, electricity consumption in Brazil grew faster than generation capacity. This situation obliged an urgent return to investment in the sector, and revitalization of the restructuring in the national electricity sector. In these circumstances, the use of renewable energy sources, such the biomass, became an option for decentralized electricity generation. Sugar cane bagasse is one of the most important biomasss residues for electricity generation. The present publication analyses an investment made in the expansion of the energy cogeneration system in an industry that produces sugar and alcohol, from sugar cane, considering the seasonal bagasse price, energy generation costs and a 10 year period. With the new cogeneration system the factory became self-sufficient in energy, with a saleable surplus of 21,240 MWh, at an average power of 4,000 kW. However, an economic analysis indicated that the best option would have been to maintain the original system and sell surplus bagasse at R$ 26.00/t.